Development of self operating water pump (Ramp Pump), a natural irrigation system for sustainable agriculture / Md Adnan Mohd Rashid - Mohd Rashid, Md Adnan (Faculty of Plantation and Agrotechnology, 2018)
Ramp pumps are currently of interest because they make use of a renewable energy resource and are naturally friendly. Ramp pumps are specially fitting for use in the creating scene as their development is fundamental and strong and they are economical and easy and simple to install and keep maintaining. Numerous attempts to analyse the intricate conduct of a ramp pump framework have been made before. However, few have been effectively converted into straightforward outline techniques and none have brought about a general strategy for a ramp pump of any size. Ramp pump also very environmental friendly because it not using a fossil fuel and electricity as energy resource. But, at the same time, ram pump only effective and has capability to operate in slope or undulating area only because it using gravity force.